Primary Problems of Preparing Children for School in Collaboration of Primary School Teachers in Preschool Educational Institutions - Ilvira Setsaliyeva (Genius Journals, 2021)
Scientific observations and research show that a person can acquire seventy percent of all information in his or her lifetime by the age of five. Indeed, during this period, a child understands the world, learns his native language, awakens love for parents, family, neighborhood, homeland, prepares the ground for lifelong learning. Psychological preparation for school education includes a readiness of the child's desire to learn, a sufficiently high level of cognitive activity and thinking operations in the desire to become a student. All components of a child’s psychological preparation for school include bringing the child into the classroom community, actively mastering the learning material in school, and fulfilling a wide range of school responsibilities. A child’s specific readiness for school is in addition to his or her general psychological readiness for school, which is determined by the child’s availability of specific knowledge, skills, and competencies needed to study academic subjects such as mathematics and mother tongue
Keywords: Preparing children for school; specific knowledge; skills; competency